2017
DOI: 10.1016/j.surfcoat.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-driven extended stability of cubic metastable Ta-Al-N and Nb-Al-N phases

Abstract: Quantum mechanical calculations had been previously applied to predict phase stability in many ternary and multinary nitride systems. While the predictions were very accurate for the Ti-Al-N system, some discrepancies between theory and experiment were obtained in the case of other systems. Namely, in the case of Ta-Al-N, the calculations tend to overestimate the minimum Al content necessary to obtain a metastable solid solution with a cubic structure. In this work, we present a comprehensive study of the impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…29,31,49 Recent reports suggested that the nanolamellae formation could be a result of a phase separation at the deposition temperature via surface diffusion or kinetically-controlled oscillating reactions at the film surface. 30,50,51 The regular morphology of the herringbone crystallites with well-developed {100} interfaces between platelets ( Fig. 2) as well as the geometrical and compositional matching at nanolamellar boundaries reported by Zalesak et al 30 in monolithic epitaxial TiAlN films suggest, however, that the nanolamellae's self-assembly is most likely a consequence of kinetically controlled oscillatory reactions at the growing film's surface described already by Bartsch et al 34 In other words, the nanolamellae are formed as a result of a sequential epitaxial overgrowth of {100} facets by individual Aland Ti-rich sub-layers.…”
Section: Discussionmentioning
confidence: 99%
“…29,31,49 Recent reports suggested that the nanolamellae formation could be a result of a phase separation at the deposition temperature via surface diffusion or kinetically-controlled oscillating reactions at the film surface. 30,50,51 The regular morphology of the herringbone crystallites with well-developed {100} interfaces between platelets ( Fig. 2) as well as the geometrical and compositional matching at nanolamellar boundaries reported by Zalesak et al 30 in monolithic epitaxial TiAlN films suggest, however, that the nanolamellae's self-assembly is most likely a consequence of kinetically controlled oscillatory reactions at the growing film's surface described already by Bartsch et al 34 In other words, the nanolamellae are formed as a result of a sequential epitaxial overgrowth of {100} facets by individual Aland Ti-rich sub-layers.…”
Section: Discussionmentioning
confidence: 99%
“…by introducing vacancies, as high temperature phases are typically of higher symmetry but also increased disorder). This has recently been verified through detailed ab initio calculations, showing that depending on the vacancy type (metallic or non-metallic sublattice) and content, δ-TaN can be stabilized over π-TaN even at 0 K 21 . For Ta-C, non-metallic vacancies are more decisive than metal vacancies for promoting a stabilization of the cubic structure, whereas for Ta-N, metallic vacancies are of crucial importance 1 , 22 .…”
Section: Introductionmentioning
confidence: 75%
“…There is as yet no consensus on the range of structural defects or exact phases present in epitaxially grown TMNs. The crystal structure that TMNs adopt is often highly dependent on stoichiometry and growth parameters 8,9 and is a subject of continued research interest. 6,10−18 An important question is whether epitaxial TMNs adopt the parent polar crystal structure of their hexagonal III-N or SiC growth substrate, P6 3 mc, or retain the desired P6 3 /mmc of the hexagonal phase, γ-Ta 2 N. The film polarity may have wide-ranging effects on the properties of devices incorporating epitaxial TMNs on polar substrates.…”
Section: ■ Introductionmentioning
confidence: 99%